PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS SCIENTIFIC APPROACH SISWA SMA KELAS X PADA MATERI FUNGI - Sari, Alvina Putri Purnama; Lepiyanto, Agil (Bioedukasi Jurnal Pendidikan Biologi, 2016)
The objective of this research is to create the product of the Student Activity Sheet (LKPD) with scientific approach based. This research uses research procedure and development 4D equipment model suggested by Thiagarajan, Semmel and Semmel. This model consist of 4 steps, they are Define, Design, Develop and Desseminate, however in this research and development, the activity is done only in to the development steps. The result of expert testing toward the design of come into being thes aspect of LKPD includes in the suitable criteria with the precentage 79,66% and  the result of the test in the material content of LKPD  also includes  suitable criteria with the precentage 81,22% and the last is the test of reading level LKPD by the students got very good criteria with presentage 80,3%.  Based on the result from expert testing and student testing,  those  show that LKPD scientific approach base has been developed properly to be used and ready to serve as one of the references in Biology learning material scientific approach based in Fungi.  Kata Kunci: lembar kegiatan peserta didik (LKPD), pendekatan saintifik.